2021
DOI: 10.2981/wlb.00781
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy and diet of the Indian desert fox Vulpes vulpes pusilla in a Prosopis juliflora invaded semi-arid grassland

Abstract: Encroachment by woody invasive plants has been recognized as a major driver of structural change in grasslands ecosystems. The impact of invasive plant-mediated changes on mammalian species from higher trophic levels is relatively less understood. This study aims to understand the impact of woody encroachment on the ecology of a relatively understudied mesopredator, the Indian desert fox Vulpes v. pusilla in a semi-arid saline grassland ecosystem in Western India. We examined the site occupancy of the Indian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In our study area, foxes may have satisfied their water intake by utilizing waterholes ( Nasanbat et al 2021 ) as the arid environment determines scarce water presence in riverbeds. Additionally, foxes inhabiting this arid terrain might have used water-rich food items (e.g., insects) to compensate for water limitations ( Dell’Arte and Leonardi 2009 ; Misher and Vanak 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study area, foxes may have satisfied their water intake by utilizing waterholes ( Nasanbat et al 2021 ) as the arid environment determines scarce water presence in riverbeds. Additionally, foxes inhabiting this arid terrain might have used water-rich food items (e.g., insects) to compensate for water limitations ( Dell’Arte and Leonardi 2009 ; Misher and Vanak 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the flora, Banni also supports many grassland specialist birds, reptiles, and mammals—e.g. the Desert fox (Misher & Vanak 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Prosopis invasion in the arid regions of India has negatively affected native herbaceous‐species richness (Kaur et al 2012) and modified habitat for threatened wildlife (Jadeja et al 2013). In Banni, Prosopis invasion has a directional impact on small mammal composition, favoring generalist rodents and canids over specialist species (Jayadevan et al 2018; Devarajan & Vanak 2020; Misher & Vanak 2021). Prosopis in Banni has increased aboveground carbon stocks (Vaibhav et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These authors also reported increased bird population in the mesquite-covered range than regions with less or no mesquite. However, Misher and Vanak (2021) discovered that the desert fox prefers more open Suaeda dominating saline habitats as compared to Prosopis dominated habitats. A negative correlation between P. juliflora density and the bird diversity has been also been reported through a study on the relationship between tree species and avifaunal diversity (Khera et al, 2009).…”
Section: Effects On Wildlifementioning
confidence: 99%